The Effect Of Electronic Word Of Mouth (E-WOM) On Tiktok Application Towards Purchase Intention Mediated By The Variables Of Information Quality, Information Quantity, Information Credibility, And Brand Image On Skintific Products - Veronita, Rika; Ariyanti, Maya; Taufik Hidayah, Riski (Publisher Cv. Inara, 2025)
The rapid growth of internet users has opened up huge opportunities for businesses to reach a wider market online, which will have an impact on the use of social media and other digital services. The phenomenon of social media has transformed conventional marketing methods, giving rise to digital marketing. With the shift from traditional word-of-mouth (WOM) to electronic word-of-mouth (eWOM), TikTok has emerged as the dominant social media platform in Indonesia, with 107.69 million users. This study aims to investigate the influence of eWOM from the TikTok platform on purchase intention for Skintific. To understand the influence of eWOM, this study will apply the Information Adoption Model (IAM), a model widely used in previous eWOM studies. This study will use a quantitative approach with a sample of 400 respondents. Data collection will be conducted using a questionnaire and analyzed using Structural Equation Modeling (SEM) with the SmartPLS 4.0.9.9 application. The results of the study indicate that respondents' evaluations of the eWOM variables, brand image, and purchase intention regarding Skintific products on TikTok fall into the good category. In this study, it was found that Information Quality, Information Credibility, Information Usefulness, Information Adoption, and Brand Image have a positive and significant effect on Purchase Intention. Specific indirect effects on Purchase Intention were also found to have a positive and significant influence. However, it was also found that Information Quantity does not have a positive and significant influence on Purchase Intention. These results highlight that Skintific needs to consistently maintain the quality of the information communicated, ensure the quantity of information provided, and uphold the credibility of information through reliable reference sources. Additionally, building a positive brand image is crucial in maintaining consumer purchase intention.